GAMBARAN MANAJEMEN DIRI MAHASISWA SAAT PANDEMI COVID-19 DITINJAU DARI JENIS KELAMIN - Rini Nurahaju (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTA Covid 19 pandemic has an impact on teaching and learning in Higher Education.Research conducted during the pandemic situation aims to find out the picture of selfmanagement in students. A total of 80 people were involved in this study. Sampling isdone by convenience or accidental sampling. The method used is descriptive quantitativemethod. Data retrieved using a measuring instrument in the form of Self-Managementscale. The methods of processing and analyzing statistical data are descriptive andinferential. This means that findings such as gender data, aspects of self-managementand other additional data are analyzed descriptively and differences in self-managementof male and female students are analyzed inferentially with the Man Whitney test in orderto describe the profile of self-management comprehensively. The results showed thatthere were no significant differences in self-management in male and female students.The level of self-management in students is in the medium category. This means that theyare capable enough to plan, organize, carry out / direct and control all activities in thispandemic situation. The implication of this research is as preliminary data to see theprofile of self-management in students.Keywords: self-management, students, co-19 pandemic